Humanitarian Translation and Refugee Policy in Indonesia: A Case of Strategic Norm Compliance - Hasan, Finahliyah (Sosiohumaniora, 2026)
This paper analyzes how the concept of humanity is translated into refugee governance practices in countries that have not ratified the 1951 Refugee Convention and the 1967 Protocol. Using Indonesia as a case study, this article seeks to answer the question how is humanitarian commitment manifested in the management of refugees in Indonesia  and how political interests influence the translation of humanitarian norms into domestic policy. Drawing on a qualitative analysis of refugee-related regulations, policy documents, and secondary literature, this article argues that Indonesia is bound by human rights conventions and has adopted international humanitarian norms into its domestic framework particularly through Presidential Regulation Number 125 of 2016. However, its implementation tends to be inconsistent and seems “half-hearted”. This trend is influenced by pressures originating from domestic problems and the dynamics of international responsibility. Therefore, the actions, or policies that the Indonesian government has claimed to be taking in the name of humanity are fraught with political implications. The absence of a sustainable political commitment to refugee protection demonstrates that refugees are merely a political tool used to acquire power and recognition on a regional and international level. This finding contributes to the growing literature on non-signatory states' responses to global refugee regimes by foregrounding the politics of translation and humanitarianism in the Southeast Asian context.